Room and Laboratory Equipment Lending Based On Smartphone Application Using QR Code Technology - Kurniawan, Yandi (Journal of Electrical, Electronics and Informatics; Vol 5 No 2 (2021): JEEI (September 2021)DO - 10.24843/JEEI.2021.v05.i02.p04, 2021)
The main problem in this research is dependency lab activities on the presence of a technician and complicated administrative process which take five procedure stages of lending at D3 and D4 Electronic Engineering polban. This research aims to create an equipment that is able to eliminate the dependency of the presence of technician, and to reduce the complicated administrative process. The QR code technology is the method used in this research to control the opening of lab doors and equipment cupboards by scanning the QR code with a mobile application. The result of this research show that the procedure borrowing of equipment facilities can be shortened from five procedurals to three procedurals. The QR Code information is able open the door of the room and laboratory cabinets by inputing password that been set at the database and able to borrow equipment that is integrated with the automatic recording of borrowing equipment.